Sleep and dreaming : (Cambridge University Press, 2003)
From the study of brainstem-based models of sleep cycle control, current research is moving toward combined brainstem/forebrain models of sleep cognition. The book presents five papers by contemporary leading scientists, and more than seventy-five commentaries on those papers by nearly all of the other distinguished authorities in the field. Topics include mechanisms of dreaming and REM sleep, memory consolidation in REM sleep, and an evolutionary hypothesis of the function of dreaming. The papers and commentaries, together with the authors' rejoinders, represent significant advances in the understanding of the sleeping and dreaming brain